Does Previous Hip Arthroscopy Affect the Clinical Outcomes of Total Hip Arthroplasty?. Issue 3 (11th March 2019) - Haynes, Jacob A.; Xiong, Ao; Nepple, Jeffrey J.; An, Tonya; Nunley, Ryan M.; Clohisy, John C.
Background: Failure of hip arthroscopy procedures and the need for subsequent total hip arthroplasty (THA) have been estimated to be as high as 16%. Prior literature has shown that failed ipsilateral knee arthroscopy may have a negative impact on the functional outcome of subsequent total knee arthroplasty. To date, there is limited information regarding the impact of failed hip arthroscopy on the clinical outcomes of subsequent primary THA. Purpose: To compare clinical outcomes in primary THA between patients with and without prior arthroscopic hip surgery. Study Design: Cohort study; Level of evidence, 3. Methods: Patients undergoing primary THA with a history of ipsilateral hip arthroscopy were matched and compared in a 1:2 manner with patients undergoing primary THA without a history of hip arthroscopy. Patient-reported clinical outcomes were measured with the modified Harris Hip Score, the University of California–Los Angeles Activity Score, and 3 subscales from the Western Ontario and McMaster Universities Osteoarthritis Index (Pain, Stiffness, and Physical Function). Results: At a mean follow-up of 42 months, there was no significant difference in any of the outcome measures between the 58 study hips and 116 matched controls. Additionally, both groups exhibited an absolute change in outcome scores that exceeded the minimum clinically important difference. Conclusion: Prior ipsilateral arthroscopic hip surgery does not adversely affect the clinical outcome of subsequent THA.